Pravozashchitnik i fizik Andrei Sakharov . Pravozashchitnik i fizik Andrei Sakharov . Human Rights Activist and Physicist Andrei Sakharov . Правозащитник и физик Андрей Сахаров - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Human rights activist Elena Bonner talks about her husband Andrei Sakharov. Featured in the program: Bonner, Elena Georgievna (Human Rights Activist) Правозащитница Елена Боннэр рассказывает о своем муже Андрее Сахарове. В программе участвуют: Боннэр, Елена Георгиевна (Правозащитница)